Synthesis, characterization and thermal behaviour on solid pyruvates of some bivalent metal ions - de Siqueira, Adriano Buzutti; de Carvalho, Cláudio Teodoro; Ionashiro, Elias Yuki; Ionashiro, Massao (Eclética Química, 2009)
Solid state M-L compounds, were M stands for bivalent Mn, Fe, Co, Ni, Cu, Zn and L is pyruvate, have been synthesized. Thermogravimetry and derivative thermogravimetry (TG/DTG), differential scanning calorimetry (DSC), X-Ray powder diffractometry, infrared spectroscopy, elemental analysis, and complexometry were used to characterize and to study the thermal behaviour of these compounds. The results led to information about the composition, dehydration, ligand denticity, and thermal decomposition of the isolated compounds.